Estimated Substitution of Tea or Coffee for Sugar-Sweetened Beverages Was Associated with Lower Type 2 Diabetes Incidence in Case–Cohort Analysis across 8 European Countries in the EPIC-InterAct Study. Issue 11 (8th August 2019) - Imamura, Fumiaki; Schulze, Matthias B; Sharp, Stephen J; Guevara, Marcela; Romaguera, Dora; Bendinelli, Benedetta; Salamanca-Fernández, Elena; Ardanaz, Eva; Arriola, Larraitz; Aune, Dagfinn; Boeing, Heiner; Dow, Courtney; et al.
ABSTRACT: Introduction: Beverage consumption is a modifiable risk factor for type 2 diabetes (T2D), but there is insufficient evidence to inform the suitability of substituting 1 type of beverage for another. Objective: The aim of this study was to estimate the risk of T2D when consumption of sugar-sweetened beverages (SSBs) was replaced with consumption of fruit juice, milk, coffee, or tea. Methods: In the European Prospective Investigation into Cancer and Nutrition (EPIC)–InterAct case–cohort study of 8 European countries ( n = 27, 662, with 12, 333 cases of incident T2D, 1992–2007), beverage consumption was estimated at baseline by dietary questionnaires. Using Prentice-weighted Cox regression adjusting for other beverages and potential confounders, we estimated associations of substituting 1 type of beverage for another on incident T2D. Results: Mean ± SD of estimated consumption of SSB was 55 ± 105 g/d. Means ± SDs for the other beverages were as follows: fruit juice, 59 ± 101 g/d; milk, 209 ± 203 g/d; coffee, 381 ± 372 g/d; and tea, 152 ± 282 g/d. Substituting coffee for SSBs by 250 g/d was associated with a 21% lower incidence of T2D (95% CI: 12%, 29%). The rate difference was −12.0 (95% CI: −20.0, −5.0) per 10, 000 person-years among adults consuming SSBs ≥250 g/d (absolute rate = 48.3/10, 000). Substituting tea for SSBs was estimated to lower T2D incidence by 22% (95% CI: 15%, 28%) or −11.0 (95% CI: −20.0, −2.6) per 10, 000 person-years, whereas substituting fruit juice or milk was estimated not to alter T2D risk significantly. Conclusions: These findings indicate a potential benefit of substituting coffee or tea for SSBs for the primary prevention of T2D and may help formulate public health recommendations on beverage consumption in different populations.